Factors associated with pharmacists’ knowledge regarding high-alert medications: a convenience sample survey in China - Ye Zhang; Yuhang Zhao; Linhui Yang; Yuanxuan Cai; Xiaofang Shangguan; Rui Huang (Acta Materia Medica, 2022)
The consequences of medication errors are more severe for high-alert medications than general drugs. Improving pharmacists’ knowledge regarding high-alert medications is important to increase drug safety and maintain patient health. This study was aimed at understanding Chinese hospital pharmacists’ knowledge regarding high-alert medications and exploring associated factors, to provide suggestions for management of high-alert medications. A total of 380 pharmacists from four hospitals in southern, northern and central China were selected through a convenience sampling method. Through a questionnaire survey, the pharmacists’ demographic sociology characteristics and knowledge regarding high-alert medications were investigated. Chi-square tests and binary logistic regression were used to analyze the factors associated with pharmacists’ knowledge regarding high-alert medications. A total of 336 valid questionnaires were returned, with an effective recovery rate of 88.4%. Among the respondents, 79.2% had high knowledge regarding high-alert medications. The analysis results show that the main factors significantly associated with pharmacists’ knowledge levels of high-alert medication were work experience and professional title, whether high alert-medication knowledge was obtained through the network channel, whether high-alert-medication knowledge was obtained through daily work practice and whether high-alert medications were double independent checked before use. Increase the sharing of work cases and knowledge cooperation among different pharmacists and departments in high-alert medications, rationally adjust and arrange the responsibilities of pharmacists, and improve the internal circulation of hospital high-alert medications are helpful to improve pharmacists’ cognitive level of high-alert medication and improve the hospital’s ability to control the risk of high-alert medication.